Предмет: Алгебра,
автор: Rimoooooochka
УМОЛЯЮ!SOS!!!!!
упростите выражение:
а) с(3^2-5с-1)-4с(3с^2-5с-2)+(3с^2-5с+1)=
б)2м(3-м+5м^2)+3м(1-м+5м^2)-5м(5м^2-m)=
в) 3а(а^2+3а+2)-4а(а^2+3а-2)+2а(а^2+3а-1)=
Ответы
Автор ответа:
0
а) с(3^2-5с-1)-4с(3с^2-5с-2)+(3с^2-5с+1)=9c - 5c^2 - c - 12c^3 + 20c^2
+8c + 3c^2 - 5c + 1 = -12c^3 + 18 c^2 + 3c + 1 = 3c(4c^2 + 6c + 3)+1
б)2m(3-m+5m^2)+3m(1-m+5m^2)-5m(5m^2-m)=6m - 2m^2 + 10m^3 +
+3m -3m^2 + 15m^3 - 25m^3 + 5m^2= 9m
в) 3а(а^2+3а+2)-4а(а^2+3а-2)+2а(а^2+3а-1)= 3a^3 +9a^2 + 6a -
-4a^3 - 12a^2 + 8a + 2a^3 +6a^2 - 2a = a^3 + 5a^2 + 12a = =a(a^2+5a+12)
+8c + 3c^2 - 5c + 1 = -12c^3 + 18 c^2 + 3c + 1 = 3c(4c^2 + 6c + 3)+1
б)2m(3-m+5m^2)+3m(1-m+5m^2)-5m(5m^2-m)=6m - 2m^2 + 10m^3 +
+3m -3m^2 + 15m^3 - 25m^3 + 5m^2= 9m
в) 3а(а^2+3а+2)-4а(а^2+3а-2)+2а(а^2+3а-1)= 3a^3 +9a^2 + 6a -
-4a^3 - 12a^2 + 8a + 2a^3 +6a^2 - 2a = a^3 + 5a^2 + 12a = =a(a^2+5a+12)
Похожие вопросы
Предмет: Математика,
автор: astana150888
Предмет: Алгебра,
автор: ivankaomelcun
Предмет: Литература,
автор: ahmaadovasamira
Предмет: Математика,
автор: anastasiyamaka1997